Development Of Digital Imaging Technique For Mapping Concrete Crack - Abdullah, Nooraishah (Universiti Sains Malaysia, 2006)
The scope of the project covers the crack study on the concrete structure of building around Pekan Parit Buntar. This purpose of this study is to investigate a non-destructive technique (NDT) using digital imaging to measure and map the dimension of concrete wall crack at regular interval along it is length. This project also studies the possibility of using GIS technique in structural crack mapping and analysis. Crack could develop due to many reasons such as overloading, corrosion of reinforcement or alkali–aggregate reaction, excessive drying shrinkage and exposure to extreme temperatures. The damage can be impact the strength of the concrete. An understanding of the evolution of crack in concrete structure due to long term natural deformation is important in civil engineering field, while quantitative measurement can be difficult to make. However, non-destructive testing (NDT) has the ability to determine the strength and durability of critical construction without damaging them and the test can carried be out on – site. Those investigated structure members can be guaranteed to be perfect without any inspection or quality control. GIS based image processing used as NDT method to determine crack. The IDRISI GIS analytical software can carry out crack profile study determining the depth of cracks. The study has pursued that modeling can be developed for crack image study and development. GIS is ideal for engineering site investigation because it is very efficient and can display information according to user defined specifications.